Teachers’ quality on use of information and communication technology tools for teaching Arabic Language in Ilorin- South Secondary Schools - Musibau , Adebayo Lawal; Ibrahim , Imam Umar (Universitas Majalengka, 2023)
Information and Communication Technology (ICT) has become an indispensable tool which has penetrated all aspects of human life. Based on this fact that the researcher examined post primary school teachers’ quality use of ICT tools for teaching Arabic Language in Ilorin South Local Government Area. Descriptive research method was adopted for this study. The population for this study comprised all secondary school Arabic teachers in Ilorin South Local Government Area while the target population is the Arabic teachers at SS I to SS III. Purposive sampling technique was used to sample 150 teachers as respondents which constituted the study sample. Researcher designed checklist was used for the instrument. Research question one with correspondent hypothesis was tested with t- test, while research questions 2,3 with similar hypotheses were tested using One-way ANOVA at alpha level of 0.05. Finding of the study shows that:(i) Significant difference exist in the Arabic teachers’ usage of ICT tools based on gender.;(ii) statistically significant difference did not exist in the Arabic teacher’s usage of information and communication technology tools based on qualification; and (iii) significant difference exist in the Arabic teacher’s use of ICT tools based on experience. Based on these findings, conclusion was reached thus Arabic tutors quality has a significant impact on the use of ICT tools in secondary, which include satellite broadcast, digital player computer and so on, also, the ministry of education should be inspecting and monitoring the use of available ICT tools and its usage in teaching Arabic language among others.